2017
DOI: 10.1155/2017/4152506
|View full text |Cite
|
Sign up to set email alerts
|

Early Bone Formation around Immediately Loaded Transitional Implants Inserted in the Human Posterior Maxilla: The Effects of Fixture Design and Surface

Abstract: Aim. To evaluate the effects of fixture design and surface on the early bone formation around immediately loaded implants inserted in the human posterior maxilla. Materials and Methods. Ten totally edentulous subjects received two transitional implants: one tapered implant with knife-edge threads/nanostructured calcium-incorporated surface (test: Anyridge®, Megagen, Gyeongbuk, South Korea) and one cylindrical implant with self-tapping threads/sandblasted surface (control: EZPlus®, Megagen). The implants were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 32 publications
(96 reference statements)
2
37
0
Order By: Relevance
“…Among the nanostructured, calcium-incorporated surfaces, there are surfaces enriched with calcium ions by a hydrothermal method, like Xpeed ® [24,32,33]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the nanostructured, calcium-incorporated surfaces, there are surfaces enriched with calcium ions by a hydrothermal method, like Xpeed ® [24,32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Although several clinical studies have shown that dental implants with a nanostructured surface enriched with calcium ions through the hydrothermal method (Xpeed ® ) can have high survival and success rates, at least in the short term [10,36,37,38,39], still little is known about the mechanism of healing these fixtures in vivo [32,33]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations